Service provided by artificial reef off Chennai:a case study - Vivekanandan, E; Venkatesan, S; MohanRaj, G (Indian Journal of Fisheries, 2011)
The fisheries service provided by an artificial reef (AR) with a pile size of 450m3 deployed at 20 m depth off Chinnandikuppam, 20 km south of Chennai wasassessed. In 16 months, the fishermen expended 3843.7 hours of hooks & linefishing in the AR ground and landed 6404 kg. The catch index was 14.2 kg/m3and the total income was Rs. 2,74,000. Compared with the income per hour ofoperation of gillnet fishing in the non-AR grounds (Rs. 52.5 kg/h), the incomewas 36% higher from hooks & line fishing in the AR ground (Rs. 71.3 kg/h).This was possible due to aggregation of high quality fish such as the snappers,emperor and carangids in the AR. Biological investigations on three residentspecies in the AR show that juvenile fish colonise in the initial months afterdeployment, grow to a larger size and spawn in the AR, indicating the service provided by the AR for enhancement of resident fish stocks.